A markerless system based on smartphones and webcam for the measure of step length, width and duration on treadmill. Issue 125 (March 2016) - Barone, V.; Verdini, F.; Burattini, L.; Di Nardo, F.; Fioretti, S.
Highlights: A markerless low cost system for the estimation of some spatial-temporal parameters of human gait. A system usable on not-instrumented treadmill. A system characterized by a very high level of automation. A system can be used to analyze up to one hundred steps. A system with precision comparable with the gold standard. Abstract: Background and objective: A markerless low cost prototype has been developed for the determination of some spatio-temporal parameters of human gait: step-length, step-width and cadence have been considered. Only a smartphone and a high-definition webcam have been used. Methods: The signals obtained by the accelerometer embedded in the smartphone are used to recognize the heel strike events, while the feet positions are calculated through image processing of the webcam stream. Step length and width are computed during gait trials on a treadmill at various speeds (3, 4 and 5 km/h). Results: Six subjects have been tested for a total of 504 steps. Results were compared with those obtained by a stereo-photogrammetric system (Elite, BTS Engineering). The maximum average errors were 3.7 cm (5.36%) for the right step length and 1.63 cm (15.16%) for the right step width at 5 km/h. The maximum average error for step duration was 0.02 s (1.69%) at 5 km/h for the right steps. Conclusion: The system is characterized by a very high level of automation that allows its use by non-expert users in non-structured environments. A low cost system able to automatically provide a reliable and repeatable evaluation of some gait events and parameters during treadmill walking, is relevant also from a clinical point of view because it allows the analysis of hundreds of steps and consequently an analysis of their variability.